Amygdalin isolated from Amygdalus mongolica protects against hepatic fibrosis in rats - Wang Jia; Zhou Hongbing; Wu Tong; Wu Peisai; Liu Quanli; Shi Songli (Acta Pharmaceutica)
The aim of this research was to investigate the effect of amygdalin on hepatic fibrosis in rats. Amygdalin was purified and identified from the seeds of Amygdalus mongo lica. Sprague Dawley rats in the control and model groups were administered water. Sprague Dawley rats were divided into the low-, middle-, and high-dose amygdalin groups that received 20, 40, and 80 mg kg−1 amygdalin, respectively. whereas the silymarin group was treated with 50 mg kg−1 silymarin. The control and model groups were administered water. Liver tissue analysis revealed significantly lower activities of ALT, AST, ALP, SOD, and MDA in the drug-treated groups compared to the model group. Serum analysis revealed significantly lower HYC and C-IV in the middle-dose amygdalin-treated group compared to the model group. The histopathological changes were less severe in the drug-treated groups as observed by the formation of pseudolobuli and decreased collagen fiber deposition. Hepatic fibrosis-related genes were expressed at significantly lower levels in the amygdalin-treated groups than in the model group. Amygdalin from A. mongolica represents a therapeutic candidate for hepatic fibrosis prevention and treatment.